حدود النظر إلى المخطوبة - دراسة فقهية مقاصدية - - إبراهيم, قعري (University of Eloued جامعة الوادي, 2019)
"موضوع هذا البحث موسوم بــــ""حدود النظر إلى المخطوبة -دراسة فقهية مقاصدية-، وإشكاليته الرئيسية التي حاول الإجابة عنها تتمحور أساسا حولحدود وضوابط نظر الخاطب إلى المخطوبة. وقد جاء الموضوع في ثلاثة مباحثَ؛ خُصِّصَ أولها لبيان تعريف حدود النظر إلى المخطوبة، ومشروعية النظر إليها، وحكمته، وحكمه، وحكم تكريره، وحكم التوكيل فيه، وجُعل ثانيها لحدود النظر إلى المخطوبة وضوابطه، في حين أن ثالثها اسْتُقرئت فيه فتاوى وآراء الفقهاء والباحثين المعاصرين في مجالي حدود النظر إلى المخطوبة، ونوازل النظر إليها. ومن النتائج الأساسية التي توصل إليها البحث أن حدود هذا النظر تتمثل فيما يظهر غالبا من المرأة نحو الرأس والرقبة والذراع والساق، كما أوصى البحث الخاطب والمخطوبة، ومن ورائهم الأولياء أن يكونوا على علم مسبق بأحكام النظر وغيره مما يتعلق بالخطبة والزواج. " "The subject of this research is entitled ""the limits of looking at the fiancée -a purposeful doctrinal study- and its main question, which it tried to answer, is mainly about the limits and controls of the fiancé's look at the fiancée. The research was divided into three sections;the first one was devoted to the definition of the limits of looking at the fiancée, the legitimacy of looking at her, its wisdom, its ruling, the ruling of repeating it, the ruling of authorization of it. The second section is about the limits of looking at the fiancée and its controls, while in the third one legal opinions and opinions of modern jurists and scholars were searched in the areas ofthe limits of looking at the fiancée and misfortunes of looking to her. One of the main findings of the research is that the limits of this looking are often shown by women towards the head, neck, arm and leg.This research is recommended thefiancéand fiancéeand their parents to be informed prior to the rulings of looking and other matters of engagement and marriage. "
مذكرة ماستر تخصص فقه مقارن
Keywords: حدود–النظر- المخطوبة; the limits - looking - the fiancée